2017
DOI: 10.1007/s10265-017-0918-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical response of hybrid black poplar tissue culture (Populus × canadensis) on water stress

Abstract: In this study, poplar tissue culture (hybrid black poplar, M1 genotype) was subjected to water stress influenced by polyethyleneglycol 6000 (100 and 200 mOsm PEG 6000). The aim of the research was to investigate the biochemical response of poplar tissue culture on water deficit regime. Antioxidant status was analyzed including antioxidant enzymes, superoxide-dismutase (SOD), catalase (CAT), guiacol-peroxidase (GPx), glutathione-peroxidase (GSH-Px), glutathione-reductase, reduced glutathione, total phenol conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…A reduction of total phenolic content in Solanum tuberosum L. exposed to drought stress in vitro was noted by Hamooh et al (2021). Results similar to ours were reported by Popović et al (2016) and Popović et al (2017), who found a significant reduction in total phenol content in leaves of Populus × canadensis genotypes at the highest level of osmotic stress (200 mOsm PEG). Finally, our findings supported the results of Roussos (2013), who evidenced the reduction of both total phenolic and flavonols' content as a consequence of the drought effect caused by the presence of mannitol.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 87%
See 2 more Smart Citations
“…A reduction of total phenolic content in Solanum tuberosum L. exposed to drought stress in vitro was noted by Hamooh et al (2021). Results similar to ours were reported by Popović et al (2016) and Popović et al (2017), who found a significant reduction in total phenol content in leaves of Populus × canadensis genotypes at the highest level of osmotic stress (200 mOsm PEG). Finally, our findings supported the results of Roussos (2013), who evidenced the reduction of both total phenolic and flavonols' content as a consequence of the drought effect caused by the presence of mannitol.…”
Section: Iforest -Biogeosciences and Forestrysupporting
confidence: 87%
“…Bettaieb et al (2011) suggested that opposite to the increment of phenolic biosynthesis in mild drought conditions, under severe drought stress, the enzymes involved in their biosynthesis such as phenylalanine ammonia-lyase (PAL) could be partially inhibited, leading to reduced phenolic content. Decreased PAL activity due to drought was observed in Euramerican poplar (Popović et al 2017). Also, Roussos (2013) found that the reduction of both phenolic and flavanols' content was accompanied by accumulation of glucose, mannitol, and pinitol, which mitigated osmotic stress.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 93%
See 1 more Smart Citation
“…CAT activity was determined using the method described by Gill and Tuteja (2010). One unit of CAT activity was defined as the amount of decreasing enzyme in absorbance of 0.01 per min, which was determined by an ultraviolet absorbance method in A 240 (Popović et al 2017). POD activity was measured by the guaiacol method (Li et al 2000), and one unit activity of which corresponded to the amount of increasing enzyme that decomposes 0.01 of substrate per min.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of sodium ions (Na + ) are toxic to plants because of their adverse effects on cellular metabolism and ion homeostasis [18][19][20]. Therefore, maintaining high and low levels of Na + in the cell, specifically in the cytoplasm, is essential for plants [19,21]. Various plant genetic strategies have been proposed to solve the salinity issue in the climate change context.…”
Section: Introductionmentioning
confidence: 99%